(x²+2xy-7x)dx+(x²+2y²-3y)dy=0
"\\dfrac{\\partial M}{\\partial y}=2x"
"\\dfrac{\\partial N}{\\partial x}=2x"
"\\dfrac{\\partial M}{\\partial y}=2x=\\dfrac{\\partial N}{\\partial x}"
The differential equation "(x^2+2xy-7x)dx+(x^2+2y^2-3y)dy=0" is an exact equation.
"\\begin{cases}\n \\dfrac{\\partial u}{\\partial x}=x^2+2xy-7x \\\\ \\\\\n \\dfrac{\\partial u}{\\partial y}=x^2+2y^2-3y\n\\end{cases}"
"u(x, y)=\\int(x^2+2xy-7x)dx+\\varphi(y)"
"=\\dfrac{1}{3}x^3+x^2y-\\dfrac{7}{2}x^2+\\varphi(y)"
"\\dfrac{\\partial u}{\\partial y}=x^2+\\varphi'(y)=x^2+2y^2-3y"
"\\varphi'(y)=2y^2-3y"
"\\varphi(y)=\\int(2y^2-3y)dy=\\dfrac{2}{3}y^3-\\dfrac{3}{2}y^2-C"
"\\dfrac{1}{3}x^3+x^2y-\\dfrac{7}{2}x^2+\\dfrac{2}{3}y^3-\\dfrac{3}{2}y^2=C"
Comments
Leave a comment